Exceptional cause of chest pain: idiopathic ascending aortitis - Mert İlker Hayıroğlu; Muhammed Keskin; Hüseyin Kuplay; Tolga Sinan Güvenç; Barış Güngör (KARE Publishing, 2017)
Idiopathic ascending aortitis is an insidious disease most often encountered during an evaluation for other cardiovascular and connective tissue diseases. To the best of our knowledge, admission to an emergency department with chest pain due to idiopathic ascending aortitis has not been reported before. Herein, the case of a 46-year-old man with chest and back pain symptoms that were discovered to be secondary solely to idiopathic ascending aortitis is described.